Efficacy of Tarunyapidikahara lepaguti in The Management of Tarunyapidika W.S.R. To Acne Vulgaris: A Case Study: Life Sciences - Bitne, Chanchal; Avinash Urkude, Dr.Minakshi; Asutkar, Dr. Sheetal; Deshpande, Dr.Mayuri (International Journal of Life Science and Pharma Research, 2023)
Tarunyapidika is one of the common health issues in youngsters. According to Ayurveda, it is under the heading of Kshudra Roga. As per modern, it is correlated with Acne vulgaris by resembling the symptoms like itching, pain, discoloration, and inflammation. Tarunyapidikahara Lepaguti is one of the modified herbal formulations that can be used to treat Acne vulgaris. Tarunyapidikahara Lepaguti includes three ingredients: Symplocos racemoser oxb, Coriandrum sativam Linn, and Acorus calamus Linn in equal parts. This Lepaguti is given to the 20 years old patient having classical signs and symptoms of Acne vulgaris for up to 21 days for local application on affected sites. In this case study, we have to evaluate the efficacy of Tarunyapidikahara Lepaguti in treating Tarunyapidika (Acne vulgaris). After the treatment, Tarunyapidikahara Lepaguti alleviated the symptoms of Acne vulgaris by reducing itching, pain, discoloration, and inflammation. Tarunyapidikahara Lepaguti is Katu Tikta Kashaya rasatmaka and Ushnaveeryatamaka reducing the Vata and Kaphadosha of Tarunyapidika (Acne vulgaris), Ruksha, Laghu and Tikshnaguna remove the obstruction of swedavahi strotsa. All drugs possess the Shothahara (anti-inflammatory), Shulaghna (analgesic), and Lekhana property, which helps in reducing the Medogarbha pidika. The conclusion that may be drawn from this study is Tarunyapidikahara Lepaguti is herbal formulation possesses antimicrobial, anti-inflammatory, and analgesic properties, which help to pacify the manifestation of Acne vulgaris with no side effects and also cost-effective.